Differentiation of Cardiomyocytes and Identification of Cardiac Conduction System Connexins Derived from Bone Marrow Mesenchymal Stem Cells of Macaca nemestrina - Agus Harsoyo; Irma Herawati Suparto; Yoga Yuniadi; Arief Boediono; Dondin Sajuthi (Bogor Agricultural University, Indonesia, 2020)
Bone marrow mesenchymal stem cells have been widely used, because plasticity, specific surface markers, self-renewal to transform into various lineages including cardiomyocytes. Information about the connexin (Cx) cardiac conduction systems of the pigtail macaque (Macaca nemestrina) is limited. This study aimed to evaluate cardiomyocyte differentiation from bone marrow mesenchymal stem cells of pigtail macaques and to clarify the Cx cardiac conduction system. Bone marrow aspirates were obtained from the proximal humerus of four adult male pigtail macaques, collected into heparinized tubes, then centrifuged to obtain mononuclear cells that were isolated and cultured in an incubator. After these cells reached 70–80% monolayer confluency as homogeneous fibroblast-like cells, they were subcultured. On the second subculture passage, the cells were pelleted to extract the mRNA, which was analysed by reverse transcription–polymerase chain reaction, and then cultured for a third passage. Cells were positive for CD73 and CD105 and the reference gene glyceraldehyde-3-phosphate dehydrogenase, and negative for CD34 and CD45. Osteogenic, chondrogenic, adipogenic, and cardiomyocyte differentiation was confirmed based on specific staining. The pigtail macaque bone marrow mesenchymal stem cells can be isolated and subcultured. The transcription of genes and translation of proteins of the connexin cardiac conduction systems was successfully identified.